Morfofisiologia de plantas de feijão-caupi sob estresse salino e adubação fosfatada - Sá, Francisco Vanies da Silva (Universidade Federal Rural do Semi-Árido, 2016)
The objective of this work was to study the effects of irrigation with saline water associated to fertilization with superphosphate in the salt balance in soil and morphophysiology bean-cowpea plants. The survey was conducted in Department of greenhouse Environmental Sciences and Technology of the Federal Rural University of the Semi-Arid (UFERSA) in Mossoró-RN, from September to December 2015. It‟s experiment was conducting a randomized block design in 5 x 3 factorial design consisting of five levels of irrigation water salinity (S1 = 0.5, S2 = 1.5; S3 = 2.5; S4 = 3.5 and S5 = 4.5 dS m-1) and management strategies fertilization with superphosphate (A1 = 60%; A2 = 100% and A3 = 140% of the recommended dose for culture), with 5 repetitions, totaling 75 experimental plants. Zebra fish were grown in pots with a capacity of 8 liters, filled with soil material and manure. The experiment was divided into four stages which were studied: 1 - Emergence and initial growth; 2 - Physiology and growth in the vegetative phase, 3 - Physiology and growth in the reproductive phase and 4 - leached salts balance and plant growth analysis. The data were submitted to analysis of variance by the test 'F' to the level of 5% probability, and in cases of significance were performed linear polynomial regression analyzes or square to the levels of salinity factor and the facts doses of phosphorus the average test was used Tukey, both at the level of 5% probability. Salinity levels above 1.5 dS m-1 culture reached the threshold (4.9 dS m-1) from the first 21 days of cultivation. Irrigation with water of high salinity increased the electrical conductivity of the saturation extract to 10.6 dS m-1. The increase in water salinity reduced the emergence, growth, photosynthetic activity and dry matter accumulation of cowpea plants. The increase of 40% on the recommendation of phosphorus fertilization of cowpea, promoted increases in growth, photosynthetic activity and plant biomass accumulation, regardless of salinity. Phosphate Fertilizer did not influence the chlorophyll a fluorescence of cowpea plants. Increased salinity affected the biomass partition of cowpea plants, with greater accumulation of dry matter in the leaves and stem, relative to the root
Keywords: Vigna unguiculata L. Walp; superfosfato simples; Salinidade; Vigna unguiculata L. Walp; Superphosphate; Salinity; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO